Organiseringen af Alternativ Politisk Deltagelse: Udkast til en Typologi - Husted, Emil (Politik, 2015)
The objective of this paper is essentially two-folded. First and foremost, the paper seeks to discuss and prob- lematize the conventional view on political participation as something primarily involving voting and formal party membership. e paper departs from the assumption that the bulk of academic literature on democracy has been overly preoccupied with conventional channels for political participation, and that this myopic view has turned a blind eye towards important enactments of democratic engagement. Building on the discourse theory of Ernesto Laclau and Chantal Mou e, the paper thus proposes a conceptualization of ‘alternative’ political participation as something involving counter-hegemonic articulations that strive to challenge the current constitution of society. e second objective of the paper is to propose a typological sketch of the organization of alternative political participation. e purpose of the typology is to provide a framework for exploring the many ways in which alternative political participation is currently being enacted. Based on two mutually constitutive axes (a political and an organizational), the typology describes four types of alternative political organizations. ese ‘ideal types’ are then exempli ed through four illustrative cases. Two of these cases – e Alternative and Occupy Wall Street – are nally examined in detail.